Transcriptome profiling revealed salt stress-responsive genes in Lilium pumilum bulbs - So, Kyongsok; Pak, Unil; Sun, Shaoying; Wang, Yiping; Yan, Hao; Zhang, Yanni (Frontiers in Plant Science, 2022)
Lilium pumilum is an important ornamental, culinary and medicinal bulbous plants with salt tolerance. However, salt tolerance of lily, particularly the bulb, has been studied relatively little, which brings challenges to the cultivation of lily varieties with high salt tolerance. Here, we performed transcriptome sequencing on the bulb organs of L. pumilum under salt stress treatment, analyzed differential gene expressed levels and then identified several key genes associated with salt stress tolerance at genome-wide scale. For the first time, we revealed the obvious response against salt stress for L. pumilum bulb organs, while distinct from those for root organs. Several key genes obtained through transcriptome analysis and DEG screening include NF-YB3 transcription factor, metallothionein type 2 protein, vicilin like seed storage protein and bidirectional sugar transporter SWEET14. Rather than typical ROS scavengers like superoxide dismutase, peroxidase, and glutathione transferase, non-typical ROS scavengers such as the metallothionein type 2 protein, and vicilin like seed storage protein were upregulated in our work. The bidirectional sugar transporter SWEET14 protein and the hormone signaling proteins such as E3-ubiquitin protein ligases, PYL4 and protein phosphatase 2C were also upregulated, suggesting the role of sugars and hormones in the bulb organ responses to salt stress. Co-expression analysis of the DEGs further confirmed that NF-YB3 transcription factor acted as a hub gene, suggesting that salt stress can promote flowering of L. pumilum. Taken together, we identified important candidate genes associated with salt tolerance of the L. pumilum bulb organs, which may provide the excellent basis for further in-depth salt tolerance mechanisms of the lily bulbs.